An introduction to alternative experimental models in monitoring economic failures - Mario Arturo Ruiz Estrada; Muhammad Tahir (Contemporary Economics, 2015)
This research paper presents four alternative experimental models for monitoring economic failures. These models include the national production function (NP-Function), the multi-level trade creation and trade diversion analytical framework, the mega-economic structures vulnerability analysis (MSV-Analysis), and the mega-economic surface interactive system. The main objective behind the proposed experimental models in economics is to analyze different macroeconomic scenarios in monitoring and warning of possible unexpected economic failure(s) under the use of a new mathematical framework and the application of multidimensional graphs. The proposed alternative experimental models are based on the application of Econographicology. Hence, our models are expected to offer policy-makers and researchers new analytical tools to study the impact and trend of economic failures in the economy of any country from a new perspective. Finally, we suggest the application of three new concepts in the study of economic failures such as Omnia Mobilis (everything is moving), the global structural imbalance principle, and the dynamic imbalance state. Therefore, our findings would certainly help both policy makers and researchers to implement and execute appropriate policies to develop their economies and to protect them from unwanted situations.
Keywords: E60; 330; Econographicology; Economic Modeling; Macroeconomic Policy; Economic Teaching; Multi-Dimensional graphs and Multi-Dimensional Physical Spaces